PENGARUH PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING PADA PEMBELAJARAN GEOGRAFI TERHADAP HASIL BELAJAR - Dian Anggraini; Budiman Tampubolon; Putri Tipa Anasi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis research was aimed to find how strong the effect of the implementation of learning model called project based learning toward students’ achievement in geography class of X IIS of SMA Kemala Bhayangkari. This research was an experimental research which used quasi experimental as the model and used the nonequivalent control group design. The population on this research was all the students of X IIS from SMA Kemala Bhayangkari with total number of students was 63 students. The technique to take the sample used on this research was random sampling. Based on the measurement of the last test on the experimental class, the mean score was 76, 75 and of the control class was 70, 69 with significant 5%. The hypothesis test the fcount was 1, 89 and the ftable was 1, 67. Based on the measurement, fcount > ftable means that Ha was acceptable. So, can conclude there was different on students’ learning achievement in geography class of  X IIS of SMA Kemala Bhayangkari after the implementation of learning model called project based learning. Based on the measurement the effect size was 0, 94 so project based learning model has medium effect toward students’ achievement in geography class of X IIS of SMA Kemala Bhayangkari.Keywords: Project Based Learning Model, Students’ Achievement.